Effects of feeding frequency on silver rasbora (Rasbora argyrotaenia) fry growth - Budi, Darmawan (Polish Journal of Natural Sciences, 2023)
As a newly domesticated species, silver rasbora (Rasbora argyrotaenia) farming needs more basic knowledge about culture procedures. Feeding management is basic crucial information in the farming of many species. This study purposes to evaluate the growth and feed efficiency of silver rasbora fry reared under different feeding frequencies. The feeding treatments of fish were divided into 4 different feeding frequency treatments (1, 2, 3, and 4 times daily), each treatment consisted of 5 replicates with 20 fish. Fish were fed ad satiation. The effects of feeding frequency on growth were determined by calculating the parameters namely body weight gain, biomass gain, specific growth rate, and feed conversion ratio. Based on the results, different feeding frequency has a significant effect (P < 0.05) on all parameters. The growth was higher with increasing feeding frequency; the highest growth was occurred on the most frequently feeding. The best growth was observed in 4 times daily feeding (final body weight: 0.45 ± 0.01 g/fish, bodyweight gain: 0.19 ± 0.00 g/fish, biomass gain: 5.58 ± 0.09 g, specific growth rate: 1.34 ± 0.06 %/day); meanwhile, feed conversion ratio decrease and showed the lowest value on 4 times daily feeding frequency treatment (1.56 ± 0.04). Referring to the growth parameters and the lowest feed conversion ratio was obtained for fish fed 4 times daily. It can be concluded that feeding 4 times daily as optimum feeding frequency in the present study resulted in better growth and feed conversion ratio during the rearing of silver rasbora.